2023
DOI: 10.1007/s40495-023-00312-4
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + Count: a Variable to Be Considered to Prioritize COVID-19 Vaccination in PLHIV

Abstract: The outbreak of the COVID-19 propagates, pressurizing the healthcare system by emphasizing and worsening the inequities. While many vaccines have shown excellent efficacy in protecting the general public from the COVID-19 infection, the efficacy of these vaccines for people living with HIV (PLHIV), especially those having a different range of CD4 + T-cell, has yet to be thoroughly investigated. Few studies have uncovered the escalated infection and death rates due to the COVID-19 infection in individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In individuals with severe COVID-19 infection, the incidence of SARS-CoV-2-specific CD4 + T cells was much lower, which implies that managing COVID-19 illness requires a strong response of CD4 + T-cell in the patients infected with COVID-19, the number of SARS-CoV-2-specific CD4 + T cells increase with age. Still, their function shifts toward Interleukin-2 (IL-2) production rather than IFN production [133]. However, there is evidence COVID-19 can lead to significant reductions in T cell numbers, particularly in patients requiring intensive care.…”
Section: Potential Mechanisms Resulting In Long Covid-19mentioning
confidence: 99%
“…In individuals with severe COVID-19 infection, the incidence of SARS-CoV-2-specific CD4 + T cells was much lower, which implies that managing COVID-19 illness requires a strong response of CD4 + T-cell in the patients infected with COVID-19, the number of SARS-CoV-2-specific CD4 + T cells increase with age. Still, their function shifts toward Interleukin-2 (IL-2) production rather than IFN production [133]. However, there is evidence COVID-19 can lead to significant reductions in T cell numbers, particularly in patients requiring intensive care.…”
Section: Potential Mechanisms Resulting In Long Covid-19mentioning
confidence: 99%
“…The CD4 count of PLHIV who are hospitalized with COVID-19 is a crucial variable to consider when predicting COVID-19 outcomes. A study from the University of Missouri revealed that PLHIV with a CD4 count of 200 cells/mm³ faced an increased risk of intensive care unit (ICU) admission, mechanical ventilation, or death (Mounika et al, 2023). Additionally, research conducted by (Shapiro et al, 2022) found an independent association between a CD4 count <350 cells/mm³, a lower nadir CD4 (<200 cells/mm³), and a lower CD4/CD8 ratio with the rate of hospitalization.…”
Section: Cd4mentioning
confidence: 99%